Vegetable oil degumming with polyimide and polyvinylidenefluoride ultrafiltration membranes - Pagliero, Cecilia Liliana (2004)
The removal of phospholipids ('degumming') is the first step in the process of refining crude vegetable oil. Membrane separation has been often proposed as an alternative to the conventional procedure (water degumming). Until now, the instability of polymeric membranes in organic solvents has been the major obstacle in applying this technique. In this work, a local synthesized polyvinylidenefluoride (PVDF) and a commercial polyimide (PI) membrane were evaluated for their flux and rejection properties during degumming of soybean oil in a laboratory-scale cross-flow ultrafiltration cell. Degumming experiments were done at different temperatures and feed flows, keeping constant both the feed concentration and the transmembrane pressure. PVDF and PI membranes gave selectivity values and permeate color that did not differ significantly from each other. Retention coefficients larger than 98% were obtained in all cases. In every experiment, a decline in permeate flux with time occurred at the beginning of the degumming process. By increasing the feed rate, a higher permeate flux was obtained. The results show that the PVDF membrane had a higher productivity than the PI one. © 2004 Society of Chemical Industry.